(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2011)
Ilka Thiessen, a professor at Vancouver Island University, is regionally specialized on Macedonia, the Balkans and Southeastern Europe. Thiessen completed her doctoral studies at the London School of Economics and Political Science; this book is in fact her doctoral dissertation. Thiessen takes interest in various theoretical - methodological innovations and interdisciplinary research on key aspects of identity, health, inequality and variety. Thiessen, in her introduction to the Macedonian edition, notes her ties to Macedonia, as well as with the young women and their families which she writes about in her book (Thiessen, 2010:13).